Risk factors for endometrial polyps to transform into endometrial cancer: insights from a bibliometric analysis - Aijie Xie; Xian Wu; Yunyi Su; Yujian Jia; Lu Yang; Ying Liu; Wei Cheng; Yonghong Lin; Xia Yu; Xiaoqin Gan (Journal of Health, Population and Nutrition)
Abstract Background Endometrial polyps (EPs) are at risk of transforming into endometrial cancer (EC). Terminal EC seriously affects women’s quality of life and places a heavy financial burden on families. Investigating the risk factors that influence the conversion of EPs to EC and preventing them from progressing further is crucial. This study attempts to map the features of published literature on risk factors and understand the frontiers and hotspots of that research by using bibliometric analysis. Methods We obtained relevant publications from 1996 to 2024 from the Web of Science Core Collection (WoSCC) on July 11, 2024. Next, CiteSpace software, the R (Version 4.3.2) package Bibliometrix, the Online Analysis Platform of Document Metrology ( http://biblimetric.com ), and a web interface for Bibliometrix were used to analyse the data. Results The analysis included 90 qualifying data points concerning the risk factors for the conversion of EPs to EC. The American Journal of Obstetrics and Gynecology was the most productive publication. The authors referenced the most were Cohen I and Ferrazzi E. After removing similar keywords, the keywords that did not have a specific meaning, the remaining keywords mainly included hysteroscopy, postmenopausal women, premenopausal, therapy, diagnosis, patients receiving tamoxifen, ultrasound, and management. The long-term management of EPs has emerged as a new research hotspot, per the trend topic. Conclusions In the published literature, age, perimenopause and postmenopausal bleeding are the most frequently studied factors for the conversion of EPs to EC, also including PCOS and polyp size. Endometrial polypectomy and long-term management may be recommended for these patients.